Strategic Positioning As A Major Driver For Enhancing Value-Added In Industrial Organizations: An Exploratory Study In The General Company For Soft Drinks - Assistant Prof .Dr. Ali kadhim Hussein; Assistant Prof. Dr. Muhammad Jabbar Hadi (Scholars Digest Publishing, 2023)
The current research begins with knowing the role played by the strategic positioning after which it is the main and essential engine to enhance the added value to take advantage of the opportunities and invest the available resources. The distinctive features that customers see as added value, and strategic positioning was expressed in a number of dimensions (customer orientation, competitor orientation, marketing ability, innovation orientation, marketing ability, and dynamic environment). to society, the added value of the environment, and the added value of relationships). Believe in strategic positioning and try to change the rules and mechanisms of competition to achieve value added). Some statistical programs were applied, the most important of which is ((SPSS.V23), and an intentional sample was chosen on which the research was applied, which is estimated at (62) respondents allocated to managers and managers of departments, divisions and units in the company under study. The research concluded with a number of conclusions, the most important of which is that the company has a proactive mentality to avoid competitors The strongest through its efforts to strategically reposition itself to protect itself from various pressures and changes in the market, and that consumers are more inclined to the brand and then the quality in the product.
Keywords: strategic positioning, added value.